Hair cortisol concentrations predict change in girls' depressive symptoms. Issue 2 (4th March 2021) - Sandstrom, Andrea; Daoust, Andrew R.; Russell, Evan; Koren, Gideon; Hayden, Elizabeth P.
ABSTRACT: Hypothalamic-Pituitary-Adrenal (HPA) axis activity is related to negative mental health outcomes, including depression. Most developmental research uses salivary cortisol to index HPA activity; however, hair cortisol concentrations (HCCs) reflect cortisol production over extended periods of time. While HCCs have been linked to adult depression, their relationship to the development of children's depressive symptoms is unclear. We assessed HCCs in 60 seven-year-old community-dwelling girls who were followed up one year later. In broader models, girls' age 7 HCCs were positively associated with age 8 depressive symptoms at a trend level, indicating that HCCs may be related to mental health early in development.